All-in-one: branched macromolecule-protected metal nanocrystals as integrated charge separation/motion centers for enhanced photocatalytic selective organic transformations. Issue 32 (30th July 2020) - Mo, Qiao-Ling; Lin, Xin; Wei, Zhi-Quan; Dai, Xiao-Cheng; Hou, Shuo; Li, Tao; Xiao, Fang-Xing
Abstract : Branched poly(ethylene imine) (bPEI)-capped metal nanocrystals are unlocked as integrated charge separation/motion centers towards the boosted photocatalytic selective organic transformation under visible light irradiation. Abstract : Precise tuning of photoinduced charge separation and transport has been an enduringly central issue in photocatalysis but has met with limited success. In particular, the controllable, accurate and simultaneous modulation on the charge (electrons/holes) transfer pathway in photocatalytic selective organic transformations has not yet been achieved. Herein, as a proof-of-principle demonstration, we report the fine tuning of charge separation/migration by smartly constructing spatially separated charge transport channels over diverse metal/transition metal chalcogenide [(M/TMC), M = Au, Ag, Pd, TMCs = ZnIn2 S4, CdIn2 S4, In2 S3, and CdS] heterostructure photosystems, which were elaborately crafted by an efficient surface ligand-triggered electrostatic self-assembly. Accordingly, tailor-made positively charged branched poly(ethylene imine) (bPEI)-capped metal nanocrystals (NCs) were controllably and uniformly anchored on the two-dimensional (2D) TMC nanosheet (NS) framework, resulting in well-defined metal/TMC heterostructures. We found that electrons photoexcited over TMC NSs could be spontaneously, smoothly and unidirectionally migrated to closely integrated metal@bPEI NCs, wherein the metal core acts as a Schottky-type electron-trapping reservoir and bPEI ligand as a hole transfer mediator, synergistically affording spatially separated charge transfer channels and expediting the charge separation/transfer efficiency. Benefiting from these merits, the self-assembled M/TMC heterostructures exhibited conspicuously boosted photoactivities in the visible light-driven selective organic transformation toward the anaerobic reduction of aromatic nitro compounds to amino derivatives, which are superior to pristine TMCs and M/TMCs without ligand encapsulation. More significantly, the self-assembly strategy and charge modulation concept are universal for diverse metal NCs and TMCs. Thus, our study provides a general and effective protocol to construct a host of metal/TMC heterostructures and stimulates new inspiration for modulating tunable charge separation/migration for substantial solar energy conversion.